Geographic Information Systems used to describe the link between the risk of Ross River virus infection and proximity to the Leschenault estuary, WA - Vally, H.; Peel, M.; Dowse, G.; Cameron, A.; Codde, Jim; Hanigan, I.; Lindsay, M. (Wiley-Blackwell Publishing Asia, 2012)
Objective: To investigate the relationship between risk of Ross River virus (RRV) infection and proximity to mosquito- breeding habitat surrounding a tidal wetland ecosystem in south-west Australia. Methods: Geographic information systems (GIS) were used to spatially map casesof RRV disease in the Leschenault region between July 1995 and June 1996. Half kilometre buffer zones were constructed around the Leschenault Estuary and associated waterways; RRV disease case counts were calculated for each zone. Results: Different relationships between RRV disease incidence and proximity to saltmarsh mosquito habitat were observed east of the Leschenault Estuary compared with an urban region to the south. Disease incidence showed a decreasing trend away from eastern margins of the Estuary, particularly for the first 2 km. In the urban region, RRV disease risk was low close to the Estuary, but increased further out and remained steady across the remainder of that region.Conclusions: The findings support an increased risk of contracting RRV disease for people residing close to eastern margins of the Leschenault Estuary.Implications: This study highlights how historical data combined with GIS can improve understanding of the epidemiology of RRV disease. This has a valuable role in assessing the risk of mosquito-borne disease for land-use planning.